Prove TanA/(1- cotA) + Cot A / (1- tanA ) = 1 + tan A + Cot A
Follow Math Help Forum on Facebook and Google+
Originally Posted by prantik007 Prove TanA/(1- cotA) + Cot A / (1- tanA ) = 1 + tan A + Cot A = tanA/( 1 - 1/tanA) + 1/tanA*tan(1-tanA) = tan^2(A)/(tanA - 1) - 1/tanA(tanA-1) = [tan^3(A) - 1]/tanA*(tanA-1) Factorize the numerator and simplify to get the result.
Can someone let me know for this
Originally Posted by martingoldstein Can someone let me know for this What do you want to know about this problem?
View Tag Cloud